(untitled) (Research, Society and Development, 2022)
Dental caries continues to be one of the main public health problems within the field of Dentistry. Its treatment depends on its stage of evolution. One of the methods that has been used today for the treatment and prevention of caries has been the Atraumatic Restorative Treatment (ART). This consists of a minimally invasive method, indicated for the treatment and also prevention of caries in the most economically and socially vulnerable population. Objective: To present the ART from the perspective of public health as a caries preventive method. Methodology: This is a literature review with a survey of works in the following databases: Virtual Health Bank (BVS) and Scientif Electronic Library Online (Scielo). Articles published in the last five years (2017 to 2022), complete and in Portuguese, were considered eligible for this research. Results: Based on the search descriptors, a total of 531 articles were initially identified. Of these, 403 were excluded because they were incomplete, 76 because they were published before 2017, 30 because they were in another language, and 10 during the title and abstract analysis. Thus, a total of 12 were selected for this study. Conclusion: ART is effective for the treatment and prevention of caries because it is a low-invasive technique, easy to apply and quick to perform, in addition to bringing less discomfort to patients.